Comparative study between intrauterine insemination following preovulatory pertubation versus intrauterine insemination alone in induced ovulation cycles in infertility patients - Dhume, Pranjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: To compare the efficacy of pertubation with low dose lignocaine before ovulation followed by intrauterine insemination versus intrauterine insemination alone in induced ovulation cycles in infertility patients. Methods: Total 60 ovulation induction cycles were studied, were randomly divided in Group A and Group B of 30 cycles each. Ovulation induction was done with clomiphene citrate / gonadotrophins. Post ovulation IUI was done in both the groups. Additionally, preovulatory pertubation with low dose lignocaine diluted in balanced salt solution was done 10-12 hrs after ovulation trigger in group A. The primary outcome conception (positive urine pregnancy test) in patients were compared between two groups. The secondary outcomes, full term pregnancy, abortion, ectopic pregnancy, procedural pain, infection, haemorrhage, and long term complications were also studied and compared. Results: Pregnancy rate was found to be slightly more in the preovulatory perturbation with low dose lignocaine and IUI group (20.6% in Group A) as compared to IUI alone group (14.7% in Group B). But the difference was not found to be statistically significant (p>0.05). The spontaneous pregnancy rates in patients with endometriosis is <5%. In the intervention group it was 37.5% in cases with endometriosis, which was encouraging. The pertubation treatment used in this study proved to be a safe treatment option without complications. Procedure was associated with mild to moderate pain in 76% patients and severe in 8.8% patients and one patient (2.9%) had syncope. Post procedure PID was noted in one patient (2.9%). Conclusions: Preovulatory perturbation followed by IUI was associated with increased clinical pregnancy rate as compared with IUI alone in induced ovulation cycles. The efficacy was more pronounced in the patients with endometriosis. It is safe and well tolerated.